Teacher Readiness to Work With English Language Learners: Arizona Context. Issue 2 (3rd April 2019) - Okhremtchouk, Irina S.; Sellu, George Sahr
Abstract: Arizona is one of six states leading the nation in English language learner (ELL) student enrollments and requiring all teachers to complete coursework in methods of teaching ELLs. This policy requirement has impacted teacher preparation programs and the field of teacher education as a whole. As such, there is a growing need to identify and evaluate factors that contribute to ELL teacher readiness. This exploratory survey study examines teacher readiness to work with ELLs in comprehensive public high schools in Arizona. This study was conducted using a survey instrument administered to in-service teachers ( n  = 444). Correlation analyses indicate that there is a strong association between preservice preparation, preservice exposure to ELLs, and the feeling of readiness to serve ELLs. The findings make a strong case for further examination of preservice teacher preparation programs, in-service professional development, and their relationship to teacher readiness.